Survival and Clinicopathological Significance of SIRT1 Expression in Cancers: A Meta-Analysis - Sun, Min; Du, Mengyu; Zhang, Wenhua; Xiong, Sisi; Gong, Xingrui; Lei, Peijie; Zha, Jin; Zhu, Hongrui; Li, Heng; Huang, Dong; Gu, Xinsheng (Frontiers in Endocrinology, 2019)
Background Silent information regulator 2 homolog 1 (SIRT1) is an evolutionarily conserved enzymes with nicotinamide adenine dinucleotide (NAD)+-dependent deacetylase activity. SIRT1 is involved in a large variety of cellular processes, such as genomic stability, energy metabolism, senescence, gene transcription, and oxidative stress. SIRT1 has long been recognized as both a tumor promoter and tumor suppressor. Its prognostic role in cancers remains controversial. Methods A meta-analysis of 13138 subjects in 63 articles from PubMed, EMBASE, and Cochrane Library was performed to evaluate survival and clinicopathological significance of SIRT1 expression in various cancers. Results The pooled results of meta-analysis showed that elevated expression of SIRT1 implies a poor overall survival (OS) of cancer patients (Hazard Ratio (HR) = 1.566, 95% CI: 1.293 - 1.895, P < 0.0001), disease free survival (DFS) (HR = 1.631, 95% CI: 1.250-2.130, P = 0.0003), event free survival (EFS) (HR = 2.534, 95% CI: 1.602 – 4.009, P = 0.0001) and progress-free survival (PFS) (HR = 3.325 95% CI: 2.762 - 4.003, P < 0.0001). Elevated SIRT1 level was associated with tumor stage (Relative Risk (RR) = 1.299, 95% CI: 1.114 - 1.514, P = 0.0008), lymph node metastasis (RR = 1.172, 95% CI: 1.010-1.360, P = 0.0363), and distant metastasis (RR = 1.562, 95% CI: 1.022 - 2.387, P = 0.0392). Meta-regression and subgroup analysis revealed that ethnic background has influence on the role of SIRT1 expression in predicting survival and clinicopathological characteristics of cancers. Overexpression of SIRT1 predicted a worse OS and higher TNM stage and lymphatic metastasis in Asian population especially in China. Conclusion Our data suggested that elevated expression of SIRT1 predicted a poor OS, DFS, EFS, PFS, but not for recurrence-free survival (RFS) and cancer-specific survival (CCS). SIRT1 overexpression was associated with higher tumor stage, lymph node metastasis, and distant metastasis. SIRT1-mediated molecular events and biological processes could be an underlying mechanism for metastasis and SIRT1 is a therapeutic target for inhibiting metastasis, leading to good prognosis.